Factors Associated with Stress, Anxiety, and Depression Patients in Hospitall - Abdul Rahman; Rizka Wahyuni; Wahyu Endang Setyowati; Dwi Heppy Rochmawati; Iskim Luthfa (PT.Mantaya Idea Batara, 2026)
Background: Psychological distress, encompassing stress, anxiety, and depression, constitutes a significant public health concern globally and is especially prevalent among psychiatric patients. Objective: to identify factors associated with stress, anxiety, and depression among psychiatric patients receiving treatment at RSKD Dadi Makassar, South Sulawesi Province, Indonesia. Methods: This quantitative cross-sectional study included 40 psychiatric patients receiving mental health services at RSKD Dadi Makassar between January and February 2026. Participants were selected through purposive sampling. Data collection utilized the Depression Anxiety Stress Scale-21 (DASS-21) questionnaire. Descriptive statistics summarized participant characteristics and levels of psychological distress. Chi-square tests assessed associations between demographic characteristics, family support, and psychological distress. Statistical significance was defined as p < 0.05. Result: Most participants were aged 26–35 years (30.0%) and male (57.5%). Moderate levels of stress, anxiety, and depression were reported by 37.5%, 35.0%, and 40.0% ofparticipants, respectively. Family support was significantly associated with depression (p= 0.021); patients with poor or no family support exhibited more severe depressive symptoms. Age was significantly associated with stress (p = 0.034), with severe stress more prevalent among patients over 45 years. Gender was significantly associated with anxiety (p = 0.028), as female patients had a higher prevalence of severe anxiety than male patients. Conclusion: Enhancing family involvement, implementing routine psychological screening, and providing targeted psychosocial interventions may improve mental health outcomes for psychiatric patients.